Judaism, Philosophy and History. On Hannah Arendt´'s Reading of Lessing, Mendelssohn and Herder in the Early 1930s - Arese, Laura (Res Publica. Revista de Historia de las Ideas Políticas, 2020)
The paper aims to reconstruct Hannah Arendt's reading of Lessing, Mendelssohn and Herder, concerning their approaches to the Jewish question, in the early 1930s. The background of this reading is the difficulty that, according to the author, European Jews demonstrate since emancipation to reach a political perspective on their own history. The paper claims that, in her reading of these philosophers, Arendt identifies a tension between reason and history, whose radicalization results in an idea of ​​reason unable to grasp the historical dimension of peoples from a political point of view. The consequence is the frustration of the political promises of Jewish emancipation, and the triumph of an ahistorical assimilation´s model. However, it will be argued that, for Arendt, the Enlightenment represented by Lessing and the romanticism that Herder embodies, do not fall along the same line of continuity. On the contrary, Arendt finds in Lessing a legacy which remains valuable for the present.
Keywords: History; Reason; Politics; Judaism; Arendt